Improvement of the open-circuit voltage of Cu2ZnSnS4 solar cells using a two-layer structure. (15th July 2015) - Tajima, Shin; Itoh, Tadayoshi; Hazama, Hirofumi; Ohishi, Keiichiro; Asahi, Ryoji
Abstract: In Cu2 ZnSnS4 (CZTS) photovoltaic cells, a low open-circuit voltage ( V OC ) principally causes low conversion efficiency. We investigated the deposition of a CZTS layer by a two-layer process to improve the V OC of the CZTS cells. In this process, the first CZTS layers near a Mo electrode have a high Cu content and the second layer near the surface has a low Cu content. The two-layer process improved the V OC of the CZTS cells from 0.66 to 0.78 V. Finally, the best CZTS cell showed a conversion efficiency of 8.8%.